Differences in Heavy Metal Accumulation in Wild and Captive Spotted Seal (Phoca largha) Pups in the Bohai Sea - Jun Luo; Weijun Guo; Zexin Liu; Dan Xu (Veterinary Medicine and Science)
ABSTRACT China established the Dalian Spotted Seal Reserve in Liaodong Bay. The spotted seal is now a nationally protected endangered species. This study analysed the correlation between heavy metal accumulation in seals' bodies and water samples from their natural Bohai Sea habitat and captive aquariums. Results showed significant differences in Al, V, Hg, Zn and Se levels among cub hair, blood and faeces (p < 0.05). Wild spotted seal pups had significantly higher levels of Al, Ar in foetal skin (p < 0.001) and V, Se in blood (p < 0.05) than captive pups. In the cub hair of wild spotted seals, Cu–Pb, Se–Hg, Se–Pb and Cd–Hg showed highly significant positive correlations (p < 0.01), and Al–Zn, Cr–Se, Cr–Hg, Cr–Cd, Mn–As, Cu–Se, Cu–Hg and Hg–Pb showed significant positive correlations (p < 0.05). In blood, Al–Ni, Cr–Ni, Mn–Ni, Ni–Cu and Ni–Cd showed significant correlations (p < 0.05), and Al showed highly significant correlations (p < 0.01) with Fe, Cu and Cd, and Mn with Cu and Cd and Cu–Cd. There were highly significant correlations (p < 0.01) between Fe–Cu in faeces and significant correlations (p < 0.05) between Ni and As and Cd, As–Cd and Hg–Pb. The results of this study indicate that marine pollution is harmful to spotted seals, and there is an urgent need to protect the healthy growth of wild spotted seals.